Digital Approaches to Music-Making for People With Dementia in Response to the COVID-19 Pandemic: Current Practice and Recommendations - Dowson, Becky; Atkinson, Rebecca; Barnes, Julie; Barone, Clare; Cutts, Nick; Donnebaum, Eleanor; Hung Hsu, Ming; Lo Coco, Irene; John, Gareth; Meadows, Grace; O'Neill, Angela; Noble, Douglas; et al. (Frontiers in Psychology, 2021)
Before COVID-19, dementia singing groups and choirs flourished, providing activity, cognitive stimulation and social support for thousands of people with dementia in the UK. Interactive music provides one of the most effective psychosocial interventions for people with dementia; it can allay agitation and promote wellbeing. Since COVID-19 has halted the delivery of in-person musical activities, it is important for the welfare of people with dementia and their carers to investigate what alternatives to live music making exist, how these alternatives are delivered and how their accessibility can be expanded. This community case study examines recent practice in online music-making in response to COVID-19 restrictions for people with dementia and their supporters, focusing on a UK context. It documents current opportunities for digital music making, and assesses the barriers and facilitators to their delivery and accessibility. Online searches of video streaming sites and social media documented what music activities were available. Expert practitioners and providers collaborated on this study and supplied input about the sessions they had been delivering, the technological challenges and solutions they had found, and the responses of the participants. Recommendations for best practice were developed and refined in consultation with these collaborators. Over 50 examples of online music activities were identified. In addition to the challenges of digital inclusion and accessibility for some older people, delivering live music online has unique challenges due to audio latency and sound quality. It is necessary to adapt the session to the technology’s limitations rather than expect to overcome these challenges. The recommendations highlight the importance of accessibility, digital safety and wellbeing of participants. They also suggest ways to optimize the quality of their musical experience. The pandemic has prompted innovative approaches to deliver activities and interventions in a digital format, and people with dementia and their carers have adapted rapidly. While online music is meeting a clear current need for social connection and cognitive stimulation, it also offers some advantages which remain relevant after COVID-19 restrictions are relaxed. The recommendations of this study are intended to be useful to musicians, dementia care practitioners and researchers during the pandemic and beyond.